واقعية ظاهرة التضخم وأثرها على اعتمادية القوائم المالية ( من وجهة نظر الأكاديميين و المختصين) (Economic studies journal, 2019)
This study aimed to know what inflation phenomenon mean in terms of reasons and types and to know the truth of inflation influence reflections on financial statements authenticity ( balance sheet, income statement ). To achieve that the questionnaire was distributed to academic specialists of Sirte university ( sample study ). The researcher also used simple statistical methods of arithmetic mean, standard deviation, and T test one sample. The study concluded that to restrict the influence of inflation phenomenon and to increase the efficiency and the trustiness of financial statements the companies must consider inflation cases and rely on innovation and alternative ways to prepare its financial statements as well as avoid other traditional methods
Keywords: inflation phenomenon; balance sheet; income statement